An Investigation of Current Endodontic Practice in Turkey - BAŞTÜRK, FATIMA BETÜL (HINDAWI LTD, 2012)
Objectives. The aim of this study was to gather information about the quality and quantity of root canal treatments carried out by general dental practitioners in Turkey. Methods. Questionnaires were given to 1400 dentists who attended the 16th National Congress organized by the Turkish Dental Association. The participants were asked to answer 34 multiple-choice questions. The questions were subdivided into 3 main topics; general information; general approach to endodontic treatment; and cleaning, shaping, and obturation of root canals. The statistical analysis was carried out by an chi(2)-test to compare the means at a significance level of P < 0.05. Results. The response rate for this study was 43%. There was a wide variation in the number of root canal treatments completed per month. Nearly 92% of practitioners stated that they never used rubber dam. The most commonly used working length determination technique was radiographic evaluation (P < 0.05). Sodium hypochlorite was the irrigant of choice with varying concentrations and AH Plus was the sealer of choice (P < 0.05). Resin composite was the most frequently used material for final restorations. Conclusions. Endodontic procedures in general practice in Turkey have differences from widely acknowledged quality guidelines. Despite the introduction of new instruments and techniques, most of the general practitioners chose conventional methods.
Keywords: ROOT-CANAL TREATMENT; FLEMISH DENTISTS; CURRENT TRENDS; GUIDELINES